The Influence Of Workload, Work Environment And Family Harmony On Job Satisfaction With Style Leadership As Moderating Case Study At The Regional Government Secretariat Anambas Islands District - Rika Karmida; Chablullah Wibisono; I Wayan Catrayasa (Brilliant International Journal Of Management And Tourism, 2023)
There are different opinions about the relationship between work environment workload and family harmony and leadership style on the level of job satisfaction. This quantitative research aims to analyze the influence of work environment workload with moderating leadership style at the Anambas Islands Regency Regional Secretariat. It was concluded that workload had a significant direct effect on job satisfaction, work environment and work-family harmony did not have a significant direct effect on job satisfaction. Then leadership style does not moderate the effect of workload on job satisfaction in the Moderation Predictor category. However, leadership style does not moderate the influence of environment and family harmony on satisfaction in the Potential Moderation category. It is recommended for leadership elements in the Anambas Regency Government to conduct a survey of employee job satisfaction, create a program of friendship activities between employees and their families, and increase their role in adjusting the workload and work environment aimed at increasing employee job satisfaction and allocating a budget for friendship activities between employees with the employee's family.